The Fantastic As a Palimpsest. Readings on «Parque Chas» (Castilla. Estudios de Literatura, 2021)
Many scholars have tried to define accurately the fantastic. Nevertheless, this paper intends to draw the attention over an aspect somehow neglected: the function of the fantastic in a dialogical relationship with many other fiction genres such as hard-boiled detective novels, urban legends, science-fiction books, or thrillers, all considered to be narrative devices used to talk in an indirect way about traumatic events. All this can be illustrated with a close reading of Parque Chas, an Argentinian comic by Barreriro and Risso, published in the magazine Fierro
Keywords: fantasy comics; Argentinian dictatorship; urban legands; Parque Chas